Extreme climatic events affecting freshwater fish reproduction in the Neotropics - E. M. Brambilla; M. R. Suiberto; A. Bialetzki; F. Porto-Foresti; M. G. Nogueira (Brazilian Journal of Biology)
Abstract This study aimed to evaluate the effect of extreme climatic events on fish reproduction by comparing the density of eggs and larvae in two consecutive, but contrasting, reproductive cycles: one atypically dry and the other with intensive rains caused by a strong El Niño event. Samples were collected fortnightly between December and February of 2014-2015 (drought cycle) and 2015-2016 (wet cycle) at six sampling sites along the Sapucaí-Mirim River, southeastern Brazil. The wet cycle presented a higher density of eggs and larvae (around 10 times more) than the drought cycle (p<0.05), with a higher proportion of families with migratory species. Principal Component Analysis explained 74.2% of environmental data variability, and all the environmental variables showed statistical differences between the two reproductive cycles, except for pH and oxidation-reduction potential. Extreme climatic events clearly affect the reproduction of freshwater fish, with a negative effect during drought periods and the opposite during wet periods. A drought period can result in the loss of a reproductive cycle, especially for flooding dependent species. Nevertheless, this reproductive failure can be compensated for by a prolonged period of intensive rain and flooding. Management actions are proposed to safeguard species in the Sapucaí-Mirin River.